Effects of Residual Anterior Lens Epithelial Cell Removal on Axial Position of Intraocular Lens after Cataract Surgery - Seung Pil Bang; Young-Sik Yoo; Jong Hwa Jun; Choun-Ki Joo (Journal of Ophthalmology)
Purpose. The aim of this study was to assess the effects of residual anterior lens epithelial cell (LEC) removal by anterior capsule polishing on the effective lens position (ELP) and axial position stability of the intraocular lens (IOL) after cataract surgery via postoperative measurement of the anterior chamber depth. Methods. We enrolled 30 patients (60 eyes) requiring bilateral cataract surgery for age-related cataracts. Meticulous anterior capsule polishing and removal of residual LECs under the capsule were performed using a bimanual irrigation/aspiration system for one randomly selected eye in each patient. The eye without polishing served as a control. ELP was measured at five different time points after surgery, and axial shifting of IOL was determined at each visit by comparison with the position at the previous visit. Results. The polishing and control groups showed significant differences with regard to the mean ELP at 1 (3.40 ± 0.29 versus 3.53 ± 0.32 mm, resp.; p=0.026) and 2 months (3.42 ± 0.32 versus 3.61 ± 0.35 mm, resp.; p=0.001) after surgery, the mean standard deviation for the five ELP values (0.087 ± 0.093 versus 0.159 ± 0.138 mm, p=0.001), and the root mean square of the change in ELP at each follow-up visit (0.124 ± 0.034 versus 0.246 ± 0.038 mm, p=0.047). The eyes in the control group exhibited a tendency for backward IOL movement with a concurrent hyperopic shift in refraction of approximately 0.2 diopter at 2 months after surgery. Conclusion. Our findings suggest that residual anterior LEC polishing enhances the axial position stability of IOLs, without any complications, after cataract surgery.